2012
DOI: 10.4088/jcp.11m07316
|View full text |Cite
|
Sign up to set email alerts
|

The Renin-Angiotensin Pathway in Posttraumatic Stress Disorder

Abstract: Objective PTSD is a debilitating stress-related illness associated with trauma exposure. The peripheral and central mechanisms mediating stress response in PTSD are incompletely understood. Recent data suggest that the renin-angiotensin pathway, essential to cardiovascular regulation, is also involved in mediating stress and anxiety. In this study, the authors examined the relationship between active treatment with blood pressure medication, including angiotensin converting enzyme inhibitors (ACE-I) and angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 37 publications
5
67
0
1
Order By: Relevance
“…These results contribute to a growing body of evidence implicating central AT 1 R activity in the expression of conditioned fear and anxiety (Khoury et al, 2012, Marvar et al, 2013, Marinzalda Mde et al, 2014, Shekhar, 2014, Shekhar et al, 2006, Johnson et al, 2013, Nylocks et al, 2015, Saavedra et al, 2006), and identify CRFergic cells as a population on which AT 1 R antagonists may act to create these effects. Further, they indicate that the fear expression-attenuating effects of AT 1 R inactivation may be caused by a decrease in fear memory consolidation (i.e., the transfer of a memory from a short-term to a long-term store in a transcription-dependent manner)—rather than an inability to acquire conditioning—as AT 1a R (+/+) and CRF-AT 1a R (−/−) mice showed similar levels of freezing during auditory fear conditioning, but 24 hours later, CRF-AT 1a R (−/−) mice displayed significantly less overall freezing than wild types.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…These results contribute to a growing body of evidence implicating central AT 1 R activity in the expression of conditioned fear and anxiety (Khoury et al, 2012, Marvar et al, 2013, Marinzalda Mde et al, 2014, Shekhar, 2014, Shekhar et al, 2006, Johnson et al, 2013, Nylocks et al, 2015, Saavedra et al, 2006), and identify CRFergic cells as a population on which AT 1 R antagonists may act to create these effects. Further, they indicate that the fear expression-attenuating effects of AT 1 R inactivation may be caused by a decrease in fear memory consolidation (i.e., the transfer of a memory from a short-term to a long-term store in a transcription-dependent manner)—rather than an inability to acquire conditioning—as AT 1a R (+/+) and CRF-AT 1a R (−/−) mice showed similar levels of freezing during auditory fear conditioning, but 24 hours later, CRF-AT 1a R (−/−) mice displayed significantly less overall freezing than wild types.…”
Section: Discussionmentioning
confidence: 52%
“…However, previous studies by our lab (Khoury et al, 2012, Marvar et al, 2013, Nylocks et al, 2015) and others (Marinzalda Mde et al, 2014, Krause et al, 2011) suggest an important role for this receptor in fear-related pathologies such as PTSD. Our current data extend these findings by demonstrating for the first time that AT 1a Rs on CRF-expressing cells contribute to conditioned fear expression without affecting fear acquisition or baseline anxiety, locomotion, blood pressure, or heart rate.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Since ARBs also exhibit partial peroxisome proliferator-activated receptor-gamma (PPAR-γ) agonistic effects and cognitive enhancement beyond blockade of AT 1 receptors (Kurtz and Klein, 2009; Min et al, 2012; Schupp et al, 2004; Tsukuda et al, 2009), candesartan could also enhance fear extinction through activation of the PPAR-γ pathway. Regardless of the mechanism, ARBs appear to be particularly useful for enhancing extinction of aversive memories and may explain why trauma-exposed patients taking ARBs had lower risk of PTSD symptoms (Khoury et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Patients with anxiety have increased risk for developing cardiovascular disease (Johannessen et al, 2006; Thurston et al, 2013) and a recent epidemiological study found that symptoms of posttraumatic stress disorder (PTSD), a type of anxiety disorder, are less severe in patients taking anti-hypertensive medications that target the renin-angiotensin-system (RAS) (Khoury et al, 2012). The effector peptide of the RAS is synthesized through a series of proteolytic cleavage events whereby renin converts angiotensinogen into angiotensin-I, which is cleaved by angiotensin converting enzyme (ACE) into angiotensin-II (Ang-II), which in turn, activates the angiotensin type 1 a receptor (AT 1a R).…”
Section: Introductionmentioning
confidence: 99%